Preparation method of pH-responsive composite hydrogel dressing with color development function

By using pH-responsive composite hydrogel dressings prepared with materials such as purple sweet potato anthocyanins, xanthan gum and polyvinyl alcohol, the problem that traditional dressings cannot monitor the wound environment and healing progress in real time, real-time monitoring and infection identification of wound pH value changes is achieved, and the scientificity and accuracy of wound care is improved.

CN119838051APending Publication Date: 2025-04-18KUNMING UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510058481.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-14
Publication Date
2025-04-18

Smart Images

  • Figure BDA0005242145900000071
    Figure BDA0005242145900000071
  • Figure HDA0005242145920000011
    Figure HDA0005242145920000011
  • Figure HDA0005242145920000012
    Figure HDA0005242145920000012
Patent Text Reader

Abstract

The invention discloses a preparation method of a pH response composite hydrogel dressing with a color development function, which comprises the following steps: dissolving purple sweet potato powder in ultrapure water, carrying out ultrasonic extraction, carrying out rotary evaporation concentration, and freeze-drying to obtain PSA powder; the preparation method comprises the following steps: dissolving zinc nitrate in ultrapure water, adding xanthan gum to obtain xanthan gum sol, dissolving polyvinyl alcohol in ultrapure water to obtain a polyvinyl alcohol solution, adding the xanthan gum sol, uniformly stirring to obtain XG-PVA sol, adding PSA powder into the XG-PVA sol, and carrying out circulating freeze thawing treatment to obtain the XG-PVA-PSA composite hydrogel dressing. The composite hydrogel dressing has excellent pH response color development performance, mechanical strength and swelling performance and good biodegradability and hydrophilicity, overcomes the defects of traditional hydrogel dressing in the aspects of real-time monitoring, infection recognition, personalized treatment and the like, improves scientificity and accuracy of wound nursing and has extremely good application and popularization prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a pH-responsive composite hydrogel dressing with a color development function, and belongs to the technical field of hydrogel bioengineering scaffolds. Background Art

[0002] Wound healing is a complex biological process, which is usually divided into four main stages: hemostasis, inflammation, proliferation and reconstruction. Hemostasis stage: After the wound is injured, the blood vessels will contract and form blood clots through the aggregation of platelets to stop bleeding. This stage lasts for several minutes to several hours. The purpose is to prevent infection and further bleeding. Inflammation stage: After hemostasis is completed, the wound will enter the inflammation stage, which usually lasts 1 to 3 days. The main function of this stage is to remove pathogens and damaged tissues in the wound. White blood cells, especially neutrophils and macrophages, will move to the wound area to engulf bacteria, dead cells and other debris to prevent infection; Proliferation stage: This stage usually occurs within 3 to 7 days after the wound and lasts for several weeks. New blood vessels are formed (i.e., angiogenesis) to provide oxygen and nutrients to the wound. In addition, fibroblasts will synthesize collagen to fill the wound defect. Skin cells also begin to proliferate, expand to the edge of the wound, and cover the wound surface; Reconstruction stage: This is the final stage of wound healing, which usually occurs weeks to months after the trauma. Collagen further matures and rearranges, and the strength of the wound gradually increases. Although the newly generated skin and tissue have not yet fully recovered to their original state, at this time, the wound becomes firmer and restores its appearance.

[0003] Dressings are materials used to cover and protect wounds. They can promote wound healing, prevent infection and reduce pain. There are many types of dressings according to their uses and functions. Common dressings are mainly the following: gauze dressings, breathable dressings, hydrocolloid dressings, hydrogel dressings, foam dressings, silver ion dressings, and alginate dressings. Hydrogels are formed by chemical or physical crosslinking of one or more hydrophilic polymers to form a three-dimensional crosslinked network structure. Due to their unique properties, hydrogel dressings can maintain a moist environment, are hygroscopic, and are suitable for a variety of wound types. In particular, hydrogels can absorb a large amount of water and swell without dissolving. Their unique internal porous crosslinked network structure can be used as a drug encapsulation carrier and provide good spatial conditions for the delivery of nutrients. Hydrogels are soft in texture and their physical properties are similar to those of biological tissues. Therefore, they have great application potential in biomedical fields such as wound healing.

[0004] With the accelerated pace of life in modern society and the increasing demand for daily necessities, traditional hydrogel dressings cannot provide real-time information on the wound healing process when used. Doctors and patients cannot accurately understand the environmental changes or healing progress of the wound, and cannot indicate whether the wound has bacterial infection or local acid-base imbalance, which may lead to the risk of infection being ignored. At this stage, the wound healing condition is mainly judged by the doctor's clinical experience, which may result in inaccurate treatment timing or misjudgment.

[0005] Purple sweet potato anthocyanidin is a kind of water-soluble natural pigment widely found in nature. It belongs to the flavonoids and has excellent biological activity, antibacterial activity, antioxidant, anti-inflammatory and other effects. It has received extensive attention in the fields of food, medicine, cosmetics and textile dyeing. In addition, anthocyanidin has excellent response color development performance and can undergo obvious color changes in the pH range of 1 to 12. Purple sweet potato anthocyanidin is generally light purple in a weakly acidic environment, dark purple in a neutral environment, and blue in an alkaline environment. This color change is due to its different ionic structures in different pH environments, and these different structures have different absorption wavelengths of ultraviolet light. Xanthan gum is mainly a highly hydrophilic anionic heteropolysaccharide produced by the microorganism Xanthomonas campestris under anaerobic conditions. It is composed of five sugar repeating units and different hydrophilic anions. It is composed of five sugar repeating units and different contents of acetyl and pyruvic acid groups. Xanthan gum has stable chemical properties, is safe and non-toxic, biodegradable, has good biocompatibility, and has immunomodulatory effects. It is often used in wound healing, drug delivery, tissue engineering, and applications involving adhesion. Polyvinyl alcohol (PVA) is a hydrophilic polymer material with good biocompatibility, non-toxicity, and good chemical stability. It can form a hydrogel through chemical or physical cross-linking. Traditional PVA hydrogels have poor mechanical strength, and applying excessive external force to them will cause permanent damage to their cross-linked structure. It is usually difficult to meet actual performance requirements. However, multifunctionality can be achieved through the modification of various composite products. Summary of the invention

[0006] The present invention provides a method for preparing a pH-responsive composite hydrogel dressing with a color development function. The obtained composite hydrogel has excellent pH-responsive color development performance, mechanical strength, swelling performance, good biodegradability and hydrophilicity, solves the deficiencies of traditional hydrogel dressings in real-time monitoring, infection identification, personalized treatment, etc., improves the scientificity and accuracy of wound care, and has excellent promotion and application prospects.

[0007] In order to achieve the above object, the technical solution of the present invention is as follows:

[0008] A method for preparing a pH-responsive composite hydrogel dressing with color development function, the specific steps are as follows:

[0009] (1) dissolving 1-4 g of purple sweet potato powder in 10-80 mL of deionized water, adjusting the pH value to 1-5 with concentrated hydrochloric acid, then ultrasonicating at 30-60° C. for 10-40 min, collecting the supernatant by centrifugation, concentrating the supernatant by rotary evaporation at 40-60° C. to 1 / 4-3 / 4 of the original volume, and freeze-drying to obtain PSA powder;

[0010] (2) dissolving zinc nitrate (ZnNO3) in ultrapure water to obtain a zinc nitrate solution, and then adding xanthan gum (XG) to obtain a xanthan gum (XG) sol;

[0011] (3) dissolving polyvinyl alcohol (PVA) in ultrapure water to obtain a polyvinyl alcohol (PVA) solution, adding the solution to the xanthan gum (XG) sol of step (2), stirring to obtain an XG-PVA sol; then adding the PSA powder of step (1), stirring to obtain an XG-PVA-PSA sol;

[0012] (4) The XG-PVA-PSA sol is subjected to a freeze-thaw cycle to obtain an XG-PVA-PSA composite hydrogel dressing.

[0013] The mass concentration of the zinc nitrate solution in step (2) is 0.1% to 2%.

[0014] The mass concentration of xanthan gum (XG) in the xanthan gum (XG) sol in step (2) is 2% to 5%.

[0015] The mass concentration of the polyvinyl alcohol (PVA) solution in step (3) is 8% to 20%.

[0016] In step (3), the volume ratio of the polyvinyl alcohol (PVA) solution to the xanthan gum (XG) sol is 1:1; the volume mass ratio (mL:g) of the XG-PVA sol to the PSA powder is 100 to 350:1.

[0017] The specific method of the freeze-thaw cycle treatment in step (4) is as follows: freezing at -40°C for 2 to 8 hours, thawing at room temperature for 2 to 4 hours, and freezing and thawing again for 2 to 6 cycles.

[0018] The pH-responsive hydrogel dressing with color development function prepared by the present invention is made into a cylinder through a mold, and its pH-responsive color development performance, mechanical properties, swelling properties, hydrophilicity, etc. are tested.

[0019] The invention adds xanthan gum, so that the purple sweet potato anthocyanin is relatively stable, and also strengthens the metal ion chelation between the anthocyanin and the zinc ion, thereby enhancing the mechanical strength of the hydrogel.

[0020] The present invention adds polyvinyl alcohol, utilizes the hydrophilicity of polyvinyl alcohol to enhance the cell adhesion of the composite hydrogel, and crystallizes the macromolecular chains of polyvinyl alcohol through freeze-thaw cycles to obtain a shaped hydrogel, thereby further enhancing the mechanical properties of the composite hydrogel.

[0021] The composite hydrogel prepared by the present invention has a complete appearance, excellent pH response color development performance, high mechanical strength, high porosity, good resilience, good hydrophilicity and swelling performance, and is suitable for use in wound repair as a tissue engineering application.

[0022] The pH-responsive hydrogel dressing prepared by the present invention can indicate changes in the pH value of the wound (such as changes in the acidic environment caused by infection) through color changes, so as to timely discover potential infection problems and thus reduce the risk of infection. It can provide doctors with more wound information, assist in the formulation of personalized treatment plans, and ensure more effective treatment effects. It solves the deficiencies of traditional hydrogel dressings in real-time monitoring, infection identification, personalized treatment, etc., and improves the scientificity and accuracy of wound care. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 Photos of XG3-PVA hydrogel and XG3-PVA-PSA 0.5% composite hydrogel prepared in Example 4 and Example 8;

[0024] Figure 2 SEM images of XG3-PVA hydrogel and XG3-PVA-PSA 0.5% composite hydrogel prepared in Example 4 and Example 8;

[0025] Figure 3 Mechanical properties of XG3-PVA hydrogel, XG4-PVA hydrogel, XG5-PVA hydrogel, XG3-PVA-PSA0.3% composite hydrogel, XG3-PVA-PSA0.5% composite hydrogel and XG3-PVA-PSA0.7% composite hydrogel prepared in Example 4, Example 5, Example 6, Example 7, Example 8 and Example 9;

[0026] Figure 4 Swelling curves of XG3-PVA hydrogel, XG3-PVA-PSA 0.3% composite hydrogel, XG3-PVA-PSA 0.5% composite hydrogel and XG3-PVA-PSA 0.7% composite hydrogel prepared in Example 4, Example 7, Example 8 and Example 9;

[0027] Figure 5 The hydrophilicity test of the XG3-PVA hydrogel and XG3-PVA-PSA 0.5% composite hydrogel prepared in Example 4 and Example 8;

[0028] Figure 6 pH response color development test of PSA powder and XG3-PVA-PSA0.5% composite hydrogel;

[0029] Figure 7 UV absorption spectra of PSA powder at different pH values. DETAILED DESCRIPTION

[0030] The present invention is further described in detail below in conjunction with the examples, but the embodiments and protection of the present invention are not limited thereto. It should be noted that if there are any details not particularly described in the examples, they can be implemented or understood by those skilled in the art with reference to the prior art.

[0031] The concentrated hydrochloric acid used for adjusting the pH value in the embodiment of the present invention is a commercially available conventional product, and its concentration is 1.18 g / mL.

[0032] Example 1

[0033] The preparation of PSA powder, the specific steps are as follows:

[0034] 1 g of purple sweet potato powder was dissolved in 10 mL of deionized water, and the pH value was adjusted to 1 with concentrated hydrochloric acid. Then, the mixture was ultrasonicated at 40°C for 40 min, and the supernatant was collected by centrifugation. The supernatant was concentrated by rotary evaporation at 40°C to 1 / 2 of the original volume, and then freeze-dried to obtain purple sweet potato anthocyanin (PSA) powder.

[0035] Example 2

[0036] The preparation of PSA powder, the specific steps are as follows:

[0037] 2 g of purple sweet potato powder was dissolved in 30 mL of deionized water, the pH value was adjusted to 2 with concentrated hydrochloric acid, and then ultrasonicated at 45 ° C for 20 min, the supernatant was collected by centrifugation, and the supernatant was concentrated by rotary evaporation at 45 ° C to 1 / 3 of the original volume, and then freeze-dried to obtain purple sweet potato anthocyanin (PSA) powder.

[0038] Example 3

[0039] The preparation of PSA powder, the specific steps are as follows:

[0040] 4 g of purple sweet potato powder was dissolved in 80 mL of deionized water, the pH value was adjusted to 5 with concentrated hydrochloric acid, and then ultrasonicated at 60°C for 10 min, the supernatant was collected by centrifugation, and the supernatant was concentrated by rotary evaporation at 50°C to 1 / 4 of the original volume, and purple sweet potato anthocyanin (PSA) powder was obtained after freeze-drying.

[0041] Example 4

[0042] The preparation of XG3-PVA hydrogel, the specific steps are as follows:

[0043] S1. Dissolve 0.1 g zinc nitrate (ZnNO3) in 10 mL ultrapure water to obtain a zinc nitrate solution, and add 0.3 g xanthan gum (XG) to the zinc nitrate solution to obtain a 3% xanthan gum (XG) sol;

[0044] S2, take 1.4 g of polyvinyl alcohol and place it in 10 mL of ultrapure water at 90°C, and stir it magnetically for 2 hours to obtain a polyvinyl alcohol solution with a mass fraction of 14%;

[0045] S3, taking the 3% xanthan gum (XG) sol of S1 and adding it to the polyvinyl alcohol solution of S2 (the volume ratio of 3% xanthan gum (XG) sol to 14% polyvinyl alcohol solution is 1:1), stirring to obtain XG3-PVA sol;

[0046] S4. Freeze the XG3-PVA sol at -40°C for 3 h and thaw at 25°C for 3 h; perform freeze-thaw cycle treatment for 4 cycles to obtain XG3-PVA hydrogel.

[0047] The concentrations of the zinc nitrate solution were adjusted to 0.3%, 0.5%, 0.7%, 1%, and 1.5%, respectively, and then the XG3-PVA hydrogel was prepared according to the process of Example 4. Tests found that when the mass concentration of zinc ions was 0.3%, 0.5%, 0.7%, and 1.5%, the compressive strength decreased significantly, and a mass concentration of 1% was selected for subsequent experiments.

[0048] The concentrations of the polyvinyl alcohol solution were adjusted to 8%, 10%, 12%, and 14%, respectively, and then XG3-PVA hydrogel was prepared according to the process of Example 4. Tests found that when the mass concentration of polyvinyl alcohol was 8%, 10%, and 12%, the compressive strength decreased significantly, and a concentration of 14% was selected for subsequent experiments.

[0049] Example 5

[0050] The preparation of XG4-PVA hydrogel, the specific steps are as follows:

[0051] S1. Dissolve 0.1 g zinc nitrate (ZnNO3) in 10 mL ultrapure water to obtain a zinc nitrate solution, and add 0.4 g xanthan gum (XG) to the zinc nitrate solution to obtain a 4% xanthan gum (XG) sol;

[0052] S2, take 1.4 g of polyvinyl alcohol and place it in 10 mL of ultrapure water at 90°C, and stir it magnetically for 2 hours to obtain a polyvinyl alcohol solution with a mass fraction of 14%;

[0053] S3, taking the 4% xanthan gum (XG) sol of S1 and adding it to the polyvinyl alcohol solution of S2 (the volume ratio of 4% xanthan gum (XG) sol to 14% polyvinyl alcohol solution is 1:1), stirring to obtain XG4-PVA sol;

[0054] S4. Freeze the XG4-PVA sol at -40°C for 3 h and thaw at 25°C for 3 h; perform freeze-thaw cycle treatment for 4 cycles to obtain XG4 / PVA hydrogel.

[0055] Example 6

[0056] The preparation of XG5-PVA hydrogel, the specific steps are as follows:

[0057] S1. Dissolve 0.1 g zinc nitrate (ZnNO3) in 10 mL ultrapure water to obtain a zinc nitrate solution, and add 0.5 g xanthan gum (XG) to the zinc nitrate solution to obtain a 5% xanthan gum (XG) sol;

[0058] S2, take 1.4 g of polyvinyl alcohol and place it in 10 mL of ultrapure water at 90°C, and stir it magnetically for 2 hours to obtain a polyvinyl alcohol solution with a mass fraction of 14%;

[0059] S3, taking 5% xanthan gum (XG) sol of S1 and adding it to the polyvinyl alcohol solution of S2 (the volume ratio of 5% xanthan gum (XG) sol to 14% polyvinyl alcohol solution is 1:1), stirring to obtain XG5-PVA sol;

[0060] S4. Freeze the XG5-PVA sol at -40°C for 3 h and thaw at 25°C for 3 h; perform freeze-thaw cycle treatment for 4 cycles to obtain XG5-PVA hydrogel.

[0061] Example 7

[0062] The preparation method of XG3-PVA-PSA 0.3% composite hydrogel, the specific steps are as follows:

[0063] S1, adding the purple sweet potato anthocyanin (PSA) powder prepared in Example 2 to the XG3-PVA sol prepared in step S3 of Example 4, the volume mass ratio of XG3-PVA sol to PSA powder mL:g ratio is 333.3:1, and stirring is performed to obtain XG3-PVA-PSA 0.3% sol;

[0064] S2. Freeze the XG3-PVA-PSA 0.3% sol at -40°C for 3 h and thaw at 25°C for 3 h; perform freeze-thaw cycle treatment for 2 cycles to obtain the XG3-PVA-PSA 0.3% composite hydrogel.

[0065] The XG3-PVA-PSA 0.3% sol was frozen at -40°C for 2 to 8 hours, thawed at room temperature for 2 to 4 hours, and then frozen and thawed again for 2 to 6 cycles to obtain a composite hydrogel with good performance.

[0066] Example 8

[0067] The preparation method of XG3-PVA-PSA0.5% composite hydrogel, the specific steps are as follows:

[0068] S1, adding the purple sweet potato anthocyanin (PSA) powder prepared in Example 2 to the XG3-PVA sol prepared in step S3 of Example 4, the volume mass ratio of XG3-PVA sol to PSA powder in mL:g is 200:1, and the mixture is stirred well to obtain XG3-PVA-PSA 0.5% sol;

[0069] S2. Freeze the XG3-PVA-PSA 0.5% sol at -40°C for 3 h and thaw at 25°C for 3 h; perform freeze-thaw cycle treatment for 2 cycles to obtain the XG3-PVA-PSA 0.5% composite hydrogel.

[0070] Example 9

[0071] The preparation method of XG3-PVA-PSA0.7% composite hydrogel, the specific steps are as follows:

[0072] S1, adding the purple sweet potato anthocyanin (PSA) powder prepared in Example 2 to the XG3-PVA sol prepared in step S3 of Example 4, the volume mass ratio of XG3-PVA sol to PSA powder mL:g ratio is 142.9:1, and stirring is performed to obtain XG3-PVA-PSA 0.7% sol;

[0073] S2. Freeze the XG3-PVA-PSA 0.7% sol at -40°C for 3 h and thaw at 25°C for 3 h; perform freeze-thaw cycle treatment for 4 cycles to obtain XG3-PVA-PSA 0.7% composite hydrogel.

[0074] like Figure 1 Shown are photos of the XG3-PVA hydrogel prepared in Example 4 and Example 8 and the pH-responsive XG3-PVA-PSA 0.5% composite hydrogel with color development function.

[0075] like Figure 2 Shown are SEM images of the XG3-PVA hydrogel prepared in Example 4 and the XG3-PVA-PSA 0.5% hydrogel in Example 8, from which obvious pore structures can be seen.

[0076] Test Example 1

[0077] The mechanical properties test of XG-PVA hydrogel and XG3-PVA-PSA composite hydrogel was carried out. The specific steps are as follows:

[0078] According to the methods of Examples 4, 5, 6, 7, 8 and 9, XG3-PVA hydrogel, XG4-PVA hydrogel, XG5-PVA hydrogel, XG3-PVA-PSA 0.3% composite hydrogel, XG3-PVA-PSA 0.5% composite hydrogel and XG3-PVA-PSA 0.7% composite hydrogel were made into cylinders with specifications of d=9 mm and h=10.00 mm; a compression test was performed on the cylinders at a speed of 1 mm / s using a universal testing machine, and a curve was plotted according to the 80% deformation, as shown in FIG. Figure 3 As shown in Figure 2, the maximum pressure of XG3-PVA hydrogel is 684.5 kPa when the deformation is 80%; the maximum pressure of XG3-PVA-PSA0.5% composite hydrogel is 708.7 kPa when the deformation is 80%. Figure 3 It can be seen that the addition of purple sweet potato anthocyanins improves the mechanical strength of the composite hydrogel by 3.5% compared with before addition.

[0079] Test Example 2

[0080] The dynamic swelling performance test was conducted on XG3-PVA hydrogel and XG3-PVA-PSA0.3%, XG3-PVA-PSA0.5%, and XG3-PVA-PSA0.7% composite hydrogels. The specific steps are as follows:

[0081] According to the methods of Example 4, Example 7, Example 8 and Example 9, XG3-PVA hydrogel, XG3-PVA-PSA 0.3% composite hydrogel, XG3-PVA-PSA 0.5% composite hydrogel and XG3-PVA-PSA 0.7% composite hydrogel were made into cylinders with specifications of d=9 mm and h=10.00 mm, and three parallel samples were set in each group. The prepared cylindrical hydrogels were freeze-dried to obtain freeze-dried hydrogels, which were weighed and recorded as W0. The cylinders made of the two composite hydrogels were respectively placed in centrifuge tubes filled with 30 mL of ultrapure water and placed in a constant temperature oscillating box for swelling. The cylinders were taken out at 0 h, 1 h, 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, 10 h, 12 h, 24 h and 32 h, and the surface moisture was wiped off with filter paper, and the weight was recorded as W S , the swelling rate of the hydrogel is calculated as follows:

[0082]

[0083] Where W S — is the mass of the hydrogel after swelling, in g;

[0084] W0—is the mass of freeze-dried hydrogel, in g.

[0085] like Figure 4As shown in the figure, the swelling rate of the XG3-PVA composite hydrogel reached an equilibrium of 601.2% at 7h; the addition of purple sweet potato anthocyanins may form hydrogen bonds or other interactions between molecules, restricting the entry of water molecules into the material, thereby reducing the swelling rate of the material and making the three-dimensional network structure of the hydrogel denser, the internal pores more dense, and the pore diameter smaller. At the same time, its maximum swelling rate decreased, but still remained above 525.73%.

[0086] Test Example 3

[0087] The hydrophilicity test of XG3-PVA hydrogel and XG3-PVA-PSA0.5% composite hydrogel was carried out, and the specific steps are as follows:

[0088] According to the method of Example 4 and Example 8, XG3-PVA hydrogel and XG3-PVA-PSA0.5% composite hydrogel were made into cylinders with specifications of d=9 mm and h=10.00 mm. Three parallel samples were set in each group. After freeze-drying, the cylindrical samples were placed on the device to be tested. 10 μL of ultrapure water was added to the surface of the composite hydrogel at a liquid addition rate of 1 mL / min. The contact angle of the water droplet was measured multiple times at room temperature and the average value was taken.

[0089] like Figure 5 As shown, the contact angle of XG3-PVA hydrogel is 70.5°, which is hydrophilic. The addition of purple sweet potato anthocyanins enhances the hydrophilicity of XG3-PVA-PSA0.5% composite hydrogel, with a contact angle of 44.0°. Hydrophilicity is conducive to cell adhesion and growth.

[0090] Test Example 4

[0091] The pH response color development test was performed on PSA powder and XG3-PVA-PSA 0.5% composite hydrogel. The specific steps are as follows:

[0092] Preparation of PBS solution: 8g sodium chloride, 0.2g potassium chloride, 1.44g disodium hydrogen phosphate, 0.24g potassium dihydrogen phosphate, 1L deionized water to volume; 5mL PBS solution was taken respectively and the pH value was adjusted to 5, 5.5, 6, 6.5, 7, 7.5, 8, 8.5, 9 with concentrated hydrochloric acid and sodium hydroxide, and a drop of PSA solution was added respectively to observe the color change, and the absorbance of PSA solution at different pH was measured with an ultraviolet spectrophotometer, and the PSA powder prepared in Example 2 and the XG3-PVA-PSA0.5% composite hydrogel prepared in Example 8 were immersed in the above solutions with different pH values ​​to observe the color change,

[0093] like Figure 6 As shown, the colors of PSA at different pH values ​​are obviously different. Figure 7The UV absorption spectrum shows that the structure of PSA is different at different pH values, which further indicates that the colors are also different. It can be seen that with the addition of PSA, the colors of XG3-PVA-PSA0.5% composite hydrogel at different pH values ​​are also significantly different.

[0094] Through the above-mentioned embodiments and test example results, it can be seen that the composite hydrogel prepared by the present invention has excellent pH response color development function and good mechanical properties, and at the same time has a porous structure; in the preparation process, no toxic cross-linking agent is used, and the raw materials used are all non-toxic and harmless polymer materials, so that the composite hydrogel prepared by this method has good biocompatibility; both the hydrophilicity and swelling properties show that the composite hydrogel is very conducive to cell attachment and growth, and the composite hydrogel is expected to be used in the field of biological wound repair.

[0095] The above descriptions are only preferred embodiments and test examples of the present invention, and are not intended to limit the scope of the present invention. Any equivalent transformations made using the contents of the present invention's specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the protection scope of the present invention.

Claims

1. A method for preparing a pH-responsive composite hydrogel dressing with color development function, characterized in that: The specific steps are as follows: (1) dissolving 1-4 g of purple sweet potato powder in 10-80 mL of deionized water, adjusting the pH value to 1-5, then ultrasonicating at 30-60° C. for 10-40 min, collecting the supernatant by centrifugation, concentrating the supernatant by rotary evaporation at 40-60° C. to 1 / 4-3 / 4 of the original volume, and freeze-drying to obtain PSA powder; (2) dissolving zinc nitrate in ultrapure water to obtain a zinc nitrate solution, and then adding xanthan gum to obtain a xanthan gum sol; (3) dissolving polyvinyl alcohol in ultrapure water to obtain a polyvinyl alcohol solution, adding the polyvinyl alcohol solution to the xanthan gum sol of step (2), stirring to obtain an XG-PVA sol; then adding the PSA powder of step (1), stirring to obtain an XG-PVA-PSA sol; (4) The XG-PVA-PSA sol is subjected to a freeze-thaw cycle to obtain an XG-PVA-PSA composite hydrogel dressing.

2. The method for preparing the pH-responsive composite hydrogel dressing with color development function according to claim 1, characterized in that: The mass concentration of the zinc nitrate solution in step (2) is 0.1% to 2%.

3. The method for preparing the pH-responsive composite hydrogel dressing with color development function according to claim 1, characterized in that: The mass concentration of xanthan gum in the xanthan gum sol in step (2) is 2% to 5%.

4. The method for preparing the pH-responsive composite hydrogel dressing with color development function according to claim 1, characterized in that: The mass concentration of the polyvinyl alcohol solution in step (3) is 8% to 20%.

5. The method for preparing the pH-responsive composite hydrogel dressing with color development function according to claim 1, characterized in that: In step (3), the volume ratio of the polyvinyl alcohol solution to the xanthan gum sol is 1:1; the volume mass ratio (mL:g) of the XG-PVA sol to the PSA powder is 100 to 350:

1.

6. The method for preparing the pH-responsive composite hydrogel dressing with color development function according to claim 1, characterized in that: The specific method of the freeze-thaw cycle treatment in step (4) is as follows: freezing at -40°C for 2 to 8 hours, thawing at room temperature for 2 to 4 hours, and freezing and thawing again for 2 to 6 cycles.